Trevathana noae, a new species of coral inhabiting barnacle (Cirripedia: Thoracica: Pyrgomatidae) - Achituv, Yair; Hosie, Andrew M. (Zootaxa, 2013)
We describe a new species from the genus Trevathana Anderson, 1992, collected from the Cocos/Keeling Islands in the Indian Ocean. Trevathana noae sp. nov. is similar to other species of Trevathana by its external shell and opercular valve morphology. It is distinct from congeners in that the tergum has a distinct spur which lacks an internal tooth in adult specimens. A key to the known species of Trevathana is given.